2015
DOI: 10.11118/actaun201563030927
|View full text |Cite
|
Sign up to set email alerts
|

Design and Operationalization of Technological Business Models

Abstract: The mechanisms of the network paradigm increasingly aff ecting the operation of companies form a new dimension of strategic management today. This applies also to the look at the design and operationalization of business models. Business models that become a source of competitive advantage in the market should have such a confi guration that will provide the company with the capability to develop and grow in value. Innovation in particular determines this capability, which is the basis for the ability to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Some of them focus on enhancing the design process [3,7,8,10], and others are used in particular situations and for particular business models [32,42,46]. Joustra et al [16] and Jong et al [14] identified five steps to support for small and medium enterprises (SMEs) to enter the circular economy.…”
Section: Design Methods and Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them focus on enhancing the design process [3,7,8,10], and others are used in particular situations and for particular business models [32,42,46]. Joustra et al [16] and Jong et al [14] identified five steps to support for small and medium enterprises (SMEs) to enter the circular economy.…”
Section: Design Methods and Toolsmentioning
confidence: 99%
“…BMC has been applied to research and design circular business models [10,11]. Jablonski [42] distinguished eleven stages of the design and operationalization of the company's technological business model embedded in the network. Parlikad et al [45] identified the information requirements for end-of-life decision making and established a possible set of characteristics of a lifecycle information system to support management.…”
Section: Design Methods and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the former domain, various studies exist [14] [15] which generally aim to articulate a procedure for small and medium enterprises (SMEs) to follow, in order to adopt and benefit from circular economy practices. One thing common to all studies is that a candidate SME needs to traverse through multiple stages to implement the mechanisms of a circular economy, ranging from five steps [16] [17], all the way to eleven stages [18]. The transition usually starts with learning the fundamental circular economy concepts, deciding on business objectives, and evaluating the readiness of the company.…”
Section: Circular Economy Business Modelsmentioning
confidence: 99%
“…A circular economy makes it possible to overcome these challenges through economic and environmental development that preserves and enhances natural Sustainability 2021, 13, 3453 2 of 18 resources and renewable flows [7]. The advantages of CE systems are attributable to the reduction in the environmental impact through the minimization of waste, the increase in economic benefits, the redesign of products, the choice of materials [8], the reduction in price volatility, and increased job growth [9,10]. The EC therefore aims to reshape global industrial systems following the ideal goal of a zero-waste economy [11].…”
Section: Introductionmentioning
confidence: 99%